2014
DOI: 10.1186/1471-2393-14-102
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of deliveries among adolescent girls at the Yaoundé central hospital

Abstract: BackgroundAdolescent pregnancies are a growing public health problem in Cameroon. We sought to study the outcome of such pregnancies, in order to inform public health action.MethodsA cross-sectional analysis of 5997 deliveries which compared the outcome of deliveries in adolescent (10–19 years old) pregnant women registered at the Yaoundé Central Hospital between 2008 and 2010 to that of their non-adolescent adult (≥ 20 years old) counterparts. Variables used for comparison included socio-demographic and obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
61
7
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 19 publications
7
61
7
8
Order By: Relevance
“…The disappearance of the higher risk of LBW among infants of adolescent mothers could be associated with lower rates of IUGR in the adolescent group compared with the adult group. Although it may be due to the small sample numbers, the present study showed an increased risk of intrauterine fetal deaths in pregnant young adolescents, consistent with other studies (2,3,8,11,14) (adjusted OR: 4.94). On the contrary, some large population studies reported that fetal death was usually either unaffected or decreased in cases with younger maternal age (3,4,13,15).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The disappearance of the higher risk of LBW among infants of adolescent mothers could be associated with lower rates of IUGR in the adolescent group compared with the adult group. Although it may be due to the small sample numbers, the present study showed an increased risk of intrauterine fetal deaths in pregnant young adolescents, consistent with other studies (2,3,8,11,14) (adjusted OR: 4.94). On the contrary, some large population studies reported that fetal death was usually either unaffected or decreased in cases with younger maternal age (3,4,13,15).…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, some large population studies reported that fetal death was usually either unaffected or decreased in cases with younger maternal age (3,4,13,15). Also, conflicting results were reported in previous investigations about neonatal mortality in adolescent pregnancy (4,6,(8)(9)(10)(11)13,14). In our study, infants from younger adolescent mothers showed a higher risk of early neonatal death related to preterm delivery and LBW (adjusted OR: 21.09), although this may be due to the small sample numbers.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This rate is lower than that recorded by Tambwe et al [8] at the University Clinics of Lubumbashi (DRC) in 1999, which was 13.9%. In African urban areas, the frequency of childbirth varies between 7% and 13% [9][10][11], while in rural areas it is more than 25% [12]. Poverty, illiteracy, and early marriages linked to cultural, ethnic and religious factors may explain this difference between the different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported (Iloki LH, 2004). Other studies, (Kemfang Ngowa JD K. J., 2015), (Fouelifack FY, 2014) and (Kumbi S1, 1999)did not find a significant difference in Apgar score as well in the first minute as in the fifth minute. An association exists between poor quality of antenatal care, fever during labor and abnormal Apgar score at birth (Fouelifack FY, 2014) 16 .…”
Section: Discussionmentioning
confidence: 92%